Medicinal chemistry approaches to malaria and other tropical diseases - Chibale, Kelly (Annual reports in medicinal chemistry, 2019)
Medicinal Chemistry Approaches to Malaria and Other Tropical Disease, Volume 53 in the Annual Reports in Medicinal Chemistry series, highlights new advances in the field, with this new volume presenting interesting chapters. Each chapter is written by an international board of authors. Key Features: Provides the authority and expertise of leading contributors from an international board of authors; Presents the latest release in the Annual Reports in Medicinal Chemistry series; Includes the latest information on Medicinal Approaches to Malaria and Other Tropical Diseases. Readership: Undergraduates, graduates, academics and researchers in the field of medicinal chemistry. --